Amelioration of Hippocampal Insulin Resistance Reduces Tau Hyperphosphorylation and Cognitive Decline Induced by Isoflurane in Mice - Peng, Liangyu; Fang, Xin; Xu, Fangxia; Liu, Shuai; Qian, Yue; Gong, Xiangdan; Zhao, Xin; Ma, Zhengliang; Xia, Tianjiao; Gu, Xiaoping (Frontiers in Aging Neuroscience, 2021)
General anesthetics can induce cognitive impairments and increase the risk of Alzheimer's disease (AD). However, the underlying mechanisms are still unknown. Our previous studies shown that long-term isoflurane exposure induced peripheral and central IR in adult mice and aggravated IR in type 2 diabetes mellitus (T2DM) mice. Clinical and preclinical studies revealed an association between impaired insulin signaling and tau pathology in AD and other tauopathies. We investigated if alleviation of hippocampal IR by the antidiabetic agent metformin could reduce tau hyperphosphorylation and cognitive decline induced by isoflurane in mice. The effects of prolonged (6-h) isoflurane anesthesia on hippocampal IR, hippocampal tau hyperphosphorylation, and hippocampus-dependent cognitive function were evaluated in wild type (WT) adult mice and the high-fat diet plus streptozotocin (HFD/STZ) mouse model of T2DM. Here we shown that isoflurane and HFD/STZ dramatically and synergistically induced hippocampal IR and fear memory impairment. Metformin pretreatment strongly ameliorated hippocampal IR and cognitive dysfunction caused by isoflurane in WT mice, but was less effective in T2DM mice. Isoflurane also induced hippocampal tau hyperphosphorylation and metformin reversed this effect. In addition, isoflurane significantly increased blood glucose levels in both adult and T2DM mice, and metformin reversed this effect as well. Administration of 25% glucose to metformin-pretreated mice induced hyperglycemia, but surprisingly did not reverse the benefits of metformin on hippocampal insulin signaling and fear memory following isoflurane anesthesia. Our findings show hippocampal IR and tau hyperphosphorylation contribute to acute isoflurane-induced cognitive dysfunction. Brief metformin treatment can mitigate these effects through a mechanism independent of glycemic control. Future studies are needed to investigate whether long-term metformin treatment can also prevent T2DM-induced hippocampal IR and cognitive decline.